Facial detection of genetic disorders - Alvi, MS (2019)
An estimated 400,000 children are born every year with rare genetic disorders that significantly affect their quality of life. Early detection and intervention can significantly improve the quality of life of these children. Craniofacial characteristics contain highly useful information for clinical geneticists for diagnosis. This thesis investigates the use of computer vision to aid in the automatic detection of genetic disorders from ordinary facial photographs. This is a non-trivial task, in part due to patient privacy concerns and the scarcity of training data. In the following, we present several approaches to overcome these challenges.